Synchronous and metachronous thoracic aortic aneurysms in patients with abdominal aortic aneurysms : a systematic review and meta‐analysis - Melo, Ryan (2020)
© 2020 The Authors. Published on behalf of the American Heart Association, Inc., by Wiley. This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made